2016
DOI: 10.3892/ol.2016.5482
|View full text |Cite
|
Sign up to set email alerts
|

Elevated microRNA-125b levels predict a worse prognosis in HER2-positive breast cancer patients

Abstract: Abstract. Breast cancer, the second most common cancer worldwide, is the leading cause of cancer-associated mortality in women, accounting for ~15% of all cancer-associated mortalities in women. The development, local invasion and metastasis of breast cancer are associated with the dysregulation and mutation of numerous genes and epigenetic mechanisms, including coding RNA and non-coding RNA, such as microRNAs (miRs/miRNAs). Previous studies have shown a dual-faced role of miR-125b in breast cancer. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…This provides further proof of the tumor suppressor role of miR-125b in breast cancer. In our study, miR-125b was found be to be upregulated with HER2-status which does not concur with the results in the literature where miR-125b was found to be significantly upregulated with HER2+ status [44].…”
Section: Discussioncontrasting
confidence: 99%
“…This provides further proof of the tumor suppressor role of miR-125b in breast cancer. In our study, miR-125b was found be to be upregulated with HER2-status which does not concur with the results in the literature where miR-125b was found to be significantly upregulated with HER2+ status [44].…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding IHC analysis scores, IHC staining was evaluated at 200× magnification using light microscopy. A semiquantitative evaluation of p53, LDHA, CCND1, p21, c‐PARP and ki67 protein was done using a method described in our previous studies …”
Section: Methodsmentioning
confidence: 99%
“…While few studies have investigated the use of miRNA serum expression levels as a predictive metric for treatment response, clinically relevant outcomes were revealed in the studies performed indicating the need for incentivizing investigations into miRNA biomarkers. For example, elevated miR-125b expression predicts poor prognosis, is associated with tumor size and TNM stage in HER2+ BC as well as poor responsiveness to paclitaxel-based neoadjuvant chemotherapy [106]. Therefore, miR-125b may be a potential predictor of clinical outcome, particularly in HER2+ BC patients receiving paclitaxel-based neoadjuvant chemotherapy.…”
Section: Mirnas As Breast Cancer Biomarkersmentioning
confidence: 99%